1992
DOI: 10.1103/physrevlett.69.644
|View full text |Cite
|
Sign up to set email alerts
|

Hard-sphere Bose gas in random external potentials

Abstract: We consider a dilute hard-sphere Bose gas in random external potentials at low temperatures, in Z) = 3, using the technique of pseudopotentials and the Bogliubov transformation. At absolute zero, the random potentials can deplete the Bose condensate, though not completely. On the other hand, they generate an amount of normal fluid equal to j the condensate depletion. This is a localization effect that can destroy superfluidity at absolute zero. General features of the superfluid density in the neighborhood of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

45
384
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(430 citation statements)
references
References 11 publications
45
384
1
Order By: Relevance
“…Many theoretical studies have examined this problem, see, e.g., Refs. [7,8,9,10,11,12,13,14]. Experimentally, numerous recent studies have considered this question in connection with trapped atomic gases [15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Many theoretical studies have examined this problem, see, e.g., Refs. [7,8,9,10,11,12,13,14]. Experimentally, numerous recent studies have considered this question in connection with trapped atomic gases [15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Since the focus of this paper is the effects of deterministic quasi-disorder on lattice bosons in harmonic potentials, it is fitting for us to place these studies in the general context of existing work on bosons in disordered environments. In the past, the effects of random disorder on interacting 3d continuum bosons have been extensively investigated [31][32][33][34][35][36][37][38][39] . It has been found that both the condensation temperature and the condensate fraction decreases with increasing disorder strength.…”
Section: Introductionmentioning
confidence: 99%
“…The first is to show that the normal fluid BEC found by Huang and Meng [3] and Giorgini et al [4] can be identified with the Bose glass insulating state found by Fisher et al [2]. Using the tight-binding Bose-Hubbard lattice model, Fisher et al [2] were able to describe an insulating state in disordered lattices which exists due to the cooperative effect of repulsive interactions and disorder.…”
mentioning
confidence: 99%
“…If interatomic interactions are also present, the interplay between the interactions and disorder can lead to a rich and complex arrangement of different quantum phases [2]. It is even possible for states to develop where the BEC (Bose-Einstein condensate) fraction is non-superfluid [3,4].…”
mentioning
confidence: 99%
See 1 more Smart Citation